2018
DOI: 10.1002/slct.201803215
|View full text |Cite
|
Sign up to set email alerts
|

Silver‐Catalyzed Arylation of (Hetero)arenes via Oxidative Benzylic C−C Bond Cleavage of Benzyl Alcohols/ Benzaldehyde

Abstract: Transition metal catalyzed direct cross coupling between benzyl alcohols/benzaldehyde and arenes/heteroarenes have been developed. By controlling electronic features of ancillary ligands, selectivity switch was observed between alkylated and arylated product. This newly developed protocol involves multi‐step alkyl oxidation and subsequent decarboxylative cross‐coupling to generate aryl‐aryl (C−C bond) scaffolds via radical pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…It is found that as recyclable heterogeneous catalyst, silver-based nanoparticles have high conversion and selectivity in alcohol oxidation or crosscoupling. [19][20][21][22] In order to improve the catalytic ability and recyclability of silver catalysts, many materials (hydrogel, cellulose, carbon fibers, magnetic materials, etc.) have been developed to support Ag nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that as recyclable heterogeneous catalyst, silver-based nanoparticles have high conversion and selectivity in alcohol oxidation or crosscoupling. [19][20][21][22] In order to improve the catalytic ability and recyclability of silver catalysts, many materials (hydrogel, cellulose, carbon fibers, magnetic materials, etc.) have been developed to support Ag nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, fewer examples of C–C bond cleavage of alcohols have been reported. Direct dehydroxymethylation of primary alcohols has been realized with transition-metal catalysts that combine dehydrogenation and decarbonylation in one pot (Scheme , eq 1) . Selective C–C bond cleavage of secondary and tertiary alcohols via β-carbon elimination, forming an organometallic intermediate and a carbonyl compound, has also been applied in organic synthesis (Scheme , eq 2).…”
mentioning
confidence: 99%